Inverse planning and inverse implanting for breast interstitial brachytherapy. Introducing a new anatomy specific breast interstitial template (ASBIT). Issue 3 (September 2018) - Karagiannis, Efstratios; Leczynski, Agnes; Tselis, Nikolaos; Psanis, Emmanouil; Steckenreiter, Oliver; Milickovic, Natasa; Bon, Dimitra; Strouthos, Iosif; Ferentinos, Konstantinos; Hass, Peter; Gademann, Günther; Baltas, Dimos; et al.
Abstract: An innovative template, based on thoracic cage surface reconstructions for breast interstitial brachytherapy was developed. Hybrid-inverse-planning-optimisation-based implantations and brachytherapy plans, using three custom anthropomorphic breast phantoms, were utilised for its validation. A user independent, inverse planning and inverse implanting technique is proposed.